Morphogenesis of the Mammalian Aortic Arch Arteries - Anderson, Robert H.; Bamforth, Simon D. (Frontiers in Cell and Developmental Biology, 2022)
The major vessels in mammals that take blood away from the heart and deliver it to the arms and the head take their origin from the aortic arch and are derived from the arteries formed within the embryonic pharyngeal arches. These pharyngeal arch arteries, initially symmetrical, form in a cranial to caudal sequence within the pharyngeal mesenchyme. They then undergo a complex process of remodeling to produce the asymmetrical brachiocephalic arteries as seen in the adult. A complex interaction between the tissues of the pharyngeal arches and the genes they express is required to ensure that arterial formation and remodeling is able to proceed normally. If this process is disrupted, life-threatening congenital cardiovascular malformations can occur, such as interruption of the aortic arch, isolation of individual arteries, or so-called vascular rings. Here, using state-of-the-art imaging techniques, we describe the morphogenesis of the arteries in humans and mice and the cardiovascular defects in the Tbx1 mutant mouse model. We provide details of the process of remodeling, clarifying also the morphogenesis of the external carotid artery and the so-called “migration” of the left subclavian artery.